An Atypical Case of Pityriasis Rosea Gigantea after Influenza Vaccination - Dimitrios Papakostas; Panagiotis G. Stavropoulos; Dafni Papafragkaki; Ekaterini Grigoraki; Georgia Avgerinou; Christina Antoniou (Karger Publishers, 2014)
Pityriasis rosea is a common erythematosquamous eruption, typically presenting along the cleavage lines of the skin. A wide spectrum of atypical manifestations may challenge even the most experienced physician. Here we report a rare case of a suberythrodermic pityriasis rosea with gigantic plaques after an influenza vaccination, and we discuss the possible triggers of atypical manifestations of such a common dermatological disease in the setting of an altered immunity.